Comparative Analysis of Private Equity Market in Poland and Other Central and Eastern European Countries; Rynek private equity w Polsce na tle pozostałych krajoẃ Europy Sŕodkowo-Wschodniej - analiza poroẃnawcza - Tomasz Sosnowski (Comparative Economic Research. Central and Eastern Europe, 2010)
The main goal of this article is an analysis of the development stage attained by the private equity market in Poland and its comparison with similar markets in other countries of Central and Eastern Europe. The main emphasis has been laid on the very essence of this source of capital and its importance for development of small and medium-sized enterprises. The performed analysis has allowed to verity the hypothesis saying that private equity funds in Poland display a greater involvement in comparison with such funds in the remaining countries of this region, which is confirmed by the value of capital invested in Polish enterprises and the value of divestments in Poland. The empirical data used in this article come from statistical reports of the European Private Equity and Venture Capital Association. – – Zasadniczym celem artykułu jest analiza stanu rozwoju rynku private equity w Polsce oraz poroẃnanie go z tego typu rynkami w innych krajach Europy Sŕodkowo- Wschodniej. Opisana zastała istota tego zŕod́ła finansowania oraz wskazano jej znaczenie dla rozwoju małych i sŕednich przedsiebiorstw. W pracy zweryfikowana została hipoteza stwierdzajaca, izḟundusze private equity w Polsce wykazuja wieksza aktywnosćńizẇ pozostałych krajach regionu, wyrazem czego jest wartosćźainwestowanych kapitałoẃ w polskie przedsiebiorstwa oraz wartosćźrealizowanych wyjsćź inwestycji w Polsce. Wykorzystane w pracy dane empiryczne pochodza z opracowanśtatystycznych European Private Equity and Venture Capital Association.
Keywords: 330